Food consumption–production response to agricultural policy and macroeconomic change in Nigeria - Ecker, Olivier; Hatzenbuehler, Patrick L. (Wiley, 2022)
Achieving agricultural transformation and farmer resilience in resource‐dependent developing countries like Nigeria is complicated by volatile macroeconomic conditions, which disrupt agricultural supply chains through income, foreign exchange, and risk‐mitigation effects. This study examines the food consumption–production linkage in Nigeria at a time when the national Agricultural Transformation Agenda was implemented and an economic crisis was unfolding. Many farm households responded to expected shocks by planting more staple foods for own consumption at the expense of agricultural commercialization, income growth, and dietary diversification. A policy initiative to improve access to modern farm inputs appeared to mitigate these adverse effects.